Dynamical and collisional evolution of Kuiper belt binaries - Brunini, Adrián (2016)
We present numerical simulations of the evolution of synthetic Trans Neptunian Binaries (TNBs) under the influence of solar perturbations, tidal friction, and collisions with the population of Classical Kuiper Belt Object (KBOs). We show that these effects, acting together, have strongly sculpted the primordial population of TNBs. If the population of Classical KBOs have a power law size distribution as the ones that are inferred from the most recent deep ecliptic surveys (Adams et al. 2014, Fraser at al. 2014), the fraction of surviving binaries at present would be of only ∼ 70 % of the primordial population. The orbits of the surviving systems match reasonably well the observed sample. Because of the impulse imparted during the collisional process, only ∼ 10 % of the objects reach total orbital circularization (e ≤ 10−4 ), and very few contact binaries should exist in the Trans Neptunian region. Ultra wide binaries are naturally obtained in number and orbital distribution similar to the ones of the observed population, as a natural result of the combined action of KCTF and collisional evolution on an initial population of tight binaries.